Effect of Recruitment, Selection and Work Environment on Employees’ Work Performance of PT Heksa Artha Sakti, Bangkalan Branch - Yuli Evitha; Eric Hernawan (Budapest International Research and Critics University, 2022)
The purpose of the research was to study the effect of the recruitment independent variables, selection and environment on the employee’s work performance of PT. Heksa Artha Sakti, Bangkalan Branch either separately or together. Determination of the effect by using the associative method used linear regression for 85 people population by using SPSS 26. Based on the results of previous research, it was found that recruitment, selection and work environment have a positive effect on employees’ work performance and the influence in percent ranges are from 30 to 50%. Simple linear regression and multiple linear regression were determined after the research data met the validity, reliability, normality, multicollinearity and heteroscedasticity tests. The significance test for simple regression was performed by t-test. Meanwhile, the significance test for multiple regression was performed by the F-test. The t-test was done by comparing tcount and ttable. And the F-Test was done by comparing Fcount and Ftable. The results obtained are the influence in percent (%) for recruitment, (X1), selection (X2) and work environment (X3) separately is 51.0%., 46.9%. and 38.1%. Meanwhile, the total effect is 55.6%.